Efficient, Robust, and Comprehensive Fault Calculation of IBR-Rich Systems Considering Diverse Controls - Xinquan Chen; Aboutaleb Haddadi; Zhe Yang; Evangelos Farantatos; Ilhan Kocar (IEEE Open Access Journal of Power and Energy)
This paper proposes a comprehensive, robust and efficient solver platform that incorporates phasor domain short circuit models of grid-forming (GFM) and grid-following (GFL) IBRs for fundamental frequency fault calculations considering various IBR controls. The proposed approach is verified through cross examination against detailed electromagnetic transient (EMT) modeling and simulations using a modified IEEE 39 bus system with multiple IBRs. The solver platform enables protection engineers to perform rapid and accurate short-circuit computations and protective relay studies in power systems with high penetration of IBRs, facilitating the assessment of fault-ride-through strategies and compliance with grid codes. This paper integrates a recently proposed derivative solution into modified augmented nodal analysis (MANA) formulation for improved numerical convergence under IBRs while treating both GFL and GFM IBR models to provide new insights and results.